Role of fundamentals of religious cultures and secular ethics lessons in spiritual morality formation among primary school children - Leshenko O. Y. (Upbringing and education: theory, metodology and practice, 2016)
as the author of this article marks, the problem of spiritual and moral development of pupils today is very acute in our society nowadays. More and more people realize that for the spiritual revival of society knowledge given by traditional education is not sufficient.
Keywords: традиции; толерантность; концепция; вера; concept; tolerance; религиозные ценности; traditions; воспитание духовно-нравственного развития; основы религиозных культур; основы светской этики; основы православной культуры; faith; religious values; upbringing of spiritual and moral development; the foundations of religious culture; the foundations of secular ethics; basics of Orthodox culture